Dynamics of a Fractional Order HIV Infection Model with Specific Functional Response and Cure Rate - Adnane Boukhouima; Khalid Hattaf; Noura Yousfi (International Journal of Differential Equations)
We propose a fractional order model in this paper to describe the dynamics of human immunodeficiency virus (HIV) infection. In the model, the infection transmission process is modeled by a specific functional response. First, we show that the model is mathematically and biologically well posed. Second, the local and global stabilities of the equilibria are investigated. Finally, some numerical simulations are presented in order to illustrate our theoretical results.